2015
DOI: 10.1017/sjp.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Support Resources, Need Satisfaction and Well-Being

Abstract: Based on Job Demands-Resources Model (JD-R), this study examines the relationships among teacher support resources, psychological need satisfaction, engagement and burnout in a sample of 282 Spanish secondary school teachers. Nine teacher psychological needs were identified based on the study of Bess and on the Self-Determination Theory (SDT). Self-report questionnaires were used to measure the constructs selected for this study and their interrelationships were examined by structural equation modeling. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 53 publications
3
12
0
7
Order By: Relevance
“…Moreover, the fully mediated model did not yield a good fit to the data. The results support the findings of other SDT research conducted with other populations in concluding that the three SDT needs mediate the relationships between environmental factors and well-being in employees (Doménech-Betoret et al, 2015; Fernet et al, 2013; Gillet et al, 2013, 2015; Graves & Luciano, 2013). These findings also support research that shows the three SDT needs do not act as one construct but rather three related constructs (e.g., Graves & Luciano, 2013; Fernet et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, the fully mediated model did not yield a good fit to the data. The results support the findings of other SDT research conducted with other populations in concluding that the three SDT needs mediate the relationships between environmental factors and well-being in employees (Doménech-Betoret et al, 2015; Fernet et al, 2013; Gillet et al, 2013, 2015; Graves & Luciano, 2013). These findings also support research that shows the three SDT needs do not act as one construct but rather three related constructs (e.g., Graves & Luciano, 2013; Fernet et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…employees (Doménech-Betoret et al, 2015;Fernet et al, 2013;Gillet et al, 2013Gillet et al, , 2015Graves & Luciano, 2013). These findings also support research that shows the three SDT needs do not act as one construct but rather three related constructs (e.g., Graves & Luciano, 2013;Fernet et al, 2013).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…According to the results of Zhang et al, students with higher scores in internal motivation show less academic burnout (4). The results of a study by Domenech-Betoret et al showed that satisfying basic needs increases students' academic engagement (27) and, consequently, reduces their academic burnout (7). The results of the current study indicated that satisfaction of autonomy and competence…”
Section: Discussionsupporting
confidence: 44%
“…Educational environments emphasizing friendship, communication between members, and mutual respect and have high quality educational services can increase the sense of coherence, autonomy, and competence among learners. Improving the culture of educational environments and the teachers' support for the autonomy of students can facilitate the fulfilment of students' basic psychological needs, leading to decreases in academic burnout (27). Accordingly, Salmela-Aro et al stated that the school atmosphere and the positive motivation received from teachers had a negative relationship with academic burnout.…”
mentioning
confidence: 99%